Construction of Compactly Supported Refinable Componentwise Polynomial Functions in ℝ2 - Yanmei Xue; Ning Bi (Abstract and Applied Analysis)
We provide a sufficient condition for constructing a class of compactly supported refinable functions with componentwise polynomial property in ℝ2. An iteration algorithm is developed to compute the polynomial on each component of the functions' support. Finally, two examples for constructing the symmetric refinable componentwise polynomial functions are given.